Urgency of Legal Regulation on Inventory Financing in Peer-to-Peer Lending to Provide Legal Protection for Lenders in Indonesia - Faisal Santiago (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
This study discusses the urgency of legal regulation of inventory financing in peer-to-peer (P2P) lending practices in Indonesia, especially in providing legal protection for lenders as lenders. Although P2P lending has been regulated in POJK No. 77/POJK.01/2016, there is no specific regulation governing inventory financing as a form of collateral, thus creating a legal vacuum that may cause risks and losses for lenders. The study uses a normative juridical method with a statutory and conceptual approach to analyze related legal aspects. The study results indicate the need for the formation of comprehensive regulations that regulate the mechanism for charging, recording, and executing inventory collateral, as well as strengthening the role of the Alternative Dispute Resolution Institution (LAPS) as an effective dispute resolution solution. Legal certainty is expected to increase lender trust, maintain the stability of the fintech platform, and encourage the growth of the national digital economy